Comparison of Anticoagulation Strategies After Left Ventricular Assist Device Implantation. Issue 2 (March 2016) - Kantorovich, Alexander; Fink, Jodie M.; Militello, Michael A.; Bauer, Seth R.; Soltesz, Edward G.; Moazami, Nader
Abstract : Appropriate early anticoagulation after left ventricular assist device (LVAD) implantation has not been established with practices ranging from no anticoagulation to early heparinization. The goal of this study was to evaluate the efficacy and morbidity of three strategies before initiating oral anticoagulation therapy. This was a noninterventional, retrospective, matched historical control cohort study. The primary and secondary endpoints were thrombotic complications (TCs) and bleeding up to 30 days post-LVAD implantation. There was a significant difference in the overall rate of TCs between strategies ( p = 0.017). The incidence of TCs was significantly lower in the heparin group versus no bridging (4.9 vs . 27.0%, p = 0.008) on univariate analysis. On multivariate analysis, heparin was independently associated with a lower odds of TCs (odds ratio [OR], 0.10; 95% confidence interval [CI], 0.01–0.85). No differences were observed in bleeding between groups ( p = 0.127) on univariate analysis; however, heparin was independently associated with increased odds of bleeding compared with no bridging on multivariate analysis (OR, 2.93; 95% CI, 1.15–7.43). Compared with no bridging, bivalirudin did not significantly differ in TC or bleeding events. Heparin seems to be the most effective regimen to use post-LVAD implantation but may increase the patient's risk for bleeding.